Respuesta :
first, subtract 17 on both sides: x²+2x-16=0
this cannot be factored, so use the quadratic formula to solve for x:
b²-4ac=2²-4(10(-16)=4+64=68
√68=2√17
so x=(-2+2√17)/2 or x=(-2-2√17)/2
x=-1+√17 or x=-1-√17
this cannot be factored, so use the quadratic formula to solve for x:
b²-4ac=2²-4(10(-16)=4+64=68
√68=2√17
so x=(-2+2√17)/2 or x=(-2-2√17)/2
x=-1+√17 or x=-1-√17
Answer:
[tex]x=-1+\sqrt{17}[/tex] and [tex]x=-1-\sqrt{17}[/tex]
Step-by-step explanation:
[tex]x^2+2x+1=17[/tex]
To solve for x , we set the right hand side =0
[tex]x^2+2x+1=17[/tex]
Subtract 17 on both sides
[tex]x^2+2x-16=0[/tex]
Now apply quadratic formula
[tex]x=\frac{-b+-\sqrt{b^2-4ac}}{2a}[/tex]
From the given f(x), the value of a=1, b=2, c=-16
Plug in all the values in the formula
[tex]x=\frac{-2+-\sqrt{2^2-4(1)(-16)}}{2(1)}[/tex]
[tex]x=\frac{-2+-\sqrt{68}}{2}[/tex]
[tex]x=\frac{-2+-2\sqrt{17}}{2}[/tex]
[tex]x=-1+-\sqrt{17}[/tex]
[tex]x=-1+\sqrt{17}[/tex] and [tex]x=-1-\sqrt{17}[/tex]